Probabilistic Liquefaction Potential Mapping in South Lebong Based on PSHA-Derived PGA - Diefi Deayuzeta; Lindung Zalbuin Mase; Fepy Supriani; Tri Bintang Pratitis; Rena Misliniyati; Khairul Amri (Bina Nusantara University, 2026)
This study evaluates liquefaction potential in South Lebong Subdistrict, Lebong Regency, Bengkulu Province, which is located in an active tectonic region influenced by the Sumatra Fault system and dominated by alluvial deposits. A probabilistic approach using the Probabilistic Seismic Hazard Analysis method to determine Peak Ground Acceleration (PGA) values for 10% and 2% probabilities of exceedance in 50 years, representing moderate to extreme earthquake conditions. South Lebong District is dominated by PGA values greater than 0.8g, particularly under the 2% probability scenario, indicating relatively high seismic hazard in the study area. Under the 10% probability scenario, several locations still show PGA values ranging from 0.4g to 0.8 g. The obtained PGA values were subsequently used to evaluate liquefaction potential through calculations of the Cyclic Stress Ratio (CSR), Cyclic Resistance Ratio (CRR), and Factor of Safety (FS). Additionally, susceptibility was assessed using the Liquefaction Potential Index (LPI) method. The results indicate that higher PGA values under the 2% probability scenario increase seismic loading intensity and liquefaction susceptibility within the study area. Based on the LPI classification, liquefaction potential under the 10% probability scenario is generally categorized as low to moderate, whereas under the 2% probability scenario, several locations shift into the moderate to severe liquefaction category. These findings indicate that liquefaction susceptibility in the South Lebong District is strongly influenced by the interaction between earthquake loading intensity and local geotechnical conditions. Therefore, the results of this study can support earthquake hazard mitigation planning and the development of safer areas that are less vulnerable to liquefaction hazards.